Glioblastoma multiforme targeted delivery of docetaxel using bevacizumab-modified nanostructured lipid carriers impair in vitro cell growth and in vivo tumor progression - Di Filippo, Leonardo Delello [UNESP] (2022)
Glioblastoma multiforme (GBM) is the most common malignant brain cancer, characterized by high invasiveness and poor prognosis. Docetaxel (DTX) is a chemotherapeutic drug with promising anti-tumor properties. However, conventional intravenous formulations exhibit side effects of systemic biodistribution and low brain bioavailability, limiting their clinical use. The current work aimed to evaluate the effect of DTX-loaded nanostructured lipid carriers (NLC) functionalized with bevacizumab (BVZ-NLC-DTX) against GBM using in vitro and in vivo models. The NLC was obtained by the fusion-emulsification method followed by sonication, with narrow size distribution, negative zeta potential, and low polydispersity index. NLC showed DTX entrapment efficiency above 90%. BVZ coupling efficiency was 62% and BVZ integrity after functionalization was confirmed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). Calorimetry studies confirmed thermal stability and molecular dispersion of DTX in the lipid matrix. NLC showed a sustained DTX release over 84 h. In vitro anti-tumor assays shown that BVZ-NLC-DTX selectively increased the cytotoxic of DTX in cells overexpressing VEGF (U87MG and A172), but not in peripheral blood mononuclear cells (PMBCs), promoting cell death by apoptosis. BVZ functionalization did not impair cellular uptake. An in vivo orthotopic rat model demonstrated that free-DTX was not capable of reducing tumor growth whereas BVZ-NLC-DTX reduced up to 70% tumor volume after 15-days of treatment. Therefore, this study contributes to understanding new nanotechnology-based vehicles capable of reaching the brain more efficiently and repurposing the use of anti-cancer drugs in GBM treatment.